Egg yolk phospholipids enriched with 1-O-octadecyl-2-oleoyl-sn-glycero-3-phospho-(N-palmitoyl) ethanolamine inhibit development of experimentally induced tumours - Karafiát, Vít; Veselý, Pavel; Dvořák, Michal (Folia biologica (Praha), 2014)
Dietary phospholipids (PLs) and their derivatives have proved active in suppression of various health problems and conditions including cancer. In this work we compared the effect of dietary phospholipids from hen egg yolk enriched with N-acyl ether-phosphatidyl ethanolamine (NAEPE) termed bioactive phospholipids (BAP+ preparation) with PLs lacking NAEPE (BAP- preparation) on the growth of transformed cells in vitro and on the promotion and progression of experimental tumours in vivo. For the in vivo experiments we used the chicken model in which liver, lung, and kidney tumours arose via natural selection from single cells initiated by experimentally introduced somatic mutations caused by insertional mutagenesis. Mutagenized animals were fed BAP+ or BAP- diet in various regimens. We observed that BAP+ at low concentrations killed cells of various tumour cell lines in culture but did not compromise viability of non-transformed cells. Oral administration of the BAP+ preparation efficiently reduced progression of all tumour types. However, it did not significantly reduce the number of already initiated tumours and their growth when BAP+ was discontinued. Our data suggest that NAEPE combined with hen egg PLs significantly interferes with tumour progression, possibly through the inhibition of tumour cell viability.
Keywords: Chick Embryo; Animals; proliferace buněk; Cell Line, Tumor; Neoplasms; nádory; nádorové buněčné linie; fosfolipidy; kultivované buňky; Cells, Cultured; ethanolaminy; modely nemocí na zvířatech; aplikace orální; Phospholipids; Cell Proliferation; Disease Models, Animal; Ethanolamines; Cell Survival; Administration, Oral; zvířata; Egg Yolk; viabilita buněk; kuřecí embryo; vaječný žloutek